Manipulation in the world of marketing - Kristina Ljubičić; Tina Vukasović (Mednarodno Inovativno Poslovanje)
Every day we are participants in various marketing advertisements. Wherever we turn at every turn, we can see at least one bit of marketing and try to communicate businesses to their products or services through marketing activities. Tempting sentences at once distract us and intrigue us to continue reading or watching a commercial or marketing view. The purpose of the research is to look at where and in what marketing activities manipulation is hidden and how and how marketing tricks using manipulation tactics influence the change in our attitude of behavior and attitude of buying certain advertised products or services. Research with a method of experiment has assessed aspects of manipulative advertising, their execution, and expected impacts on consumer behaviour in general about any purchase of a product or service worldwide. Analysis of the collected primary data revealed that manipulation in marketing is quite common and occurs at every step and has begun to be one of the main players when creating marketing ventures and actions.